1990
DOI: 10.1042/bj2680287
|View full text |Cite
|
Sign up to set email alerts
|

Structure and expression of the human cystatin C gene

Abstract: The structural organization of the gene for the human cysteine-proteinase inhibitor cystatin C was studied. Restriction-endonuclease digests of human genomic DNA hybridized with human cystatin C cDNA and genomic probes produced patterns consistent with a single cystatin C gene and, also, the presence of six closely related sequences in the human genome. A 30 kb restriction map covering the genomic region of the cystatin C gene was constructed. The positions of three polymorphic restriction sites, found at exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
316
0
15

Year Published

1997
1997
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 558 publications
(341 citation statements)
references
References 29 publications
(29 reference statements)
10
316
0
15
Order By: Relevance
“…5 It is produced by all nucleated cells at a constant rate, 6 freely ®ltered in the glomeruli and reabsorbed and catabolized in the proximal tubular cells. 7 The characteristics of cystatin C indicates that its serum concentration is mainly determined by GFR making cystatin C an endogenous parameter of GFR.…”
Section: Introductionmentioning
confidence: 99%
“…5 It is produced by all nucleated cells at a constant rate, 6 freely ®ltered in the glomeruli and reabsorbed and catabolized in the proximal tubular cells. 7 The characteristics of cystatin C indicates that its serum concentration is mainly determined by GFR making cystatin C an endogenous parameter of GFR.…”
Section: Introductionmentioning
confidence: 99%
“…broadly expressed [11]. Although it is well established by studies in itro that the cystatins are cysteine protease inhibitors with specificities against papain-like cysteine proteases such as cathepsins B, S, H and L, the functions of these proteins in i o are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Studies performed on sections of human tissue or cell lines have shown that when visualised by immunohistochemical labelling or messenger RNA detected by Northern blot, the protein is present in all types of cells studied (25)(26)(27). CysC is coded by a housekeeping gene, i.e., a gene expressed both constitutively and in an unregulated manner, the classical argument supporting constant production (25,28).…”
Section: Is the Production Of Cysc Constant?mentioning
confidence: 99%